2015
DOI: 10.1037/a0039596
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a web-based intervention to reduce distress among students with a history of interpersonal violence.

Abstract: Objective: Many college students have a history of interpersonal violence (IPV) and are thus at risk of greater mental health problems. This study evaluated the efficacy of a web-based stress management program targeting the established protective factor of present control in promoting well-being among students with and without a history of IPV. Method: Students from an introductory psychology course were randomly assigned in a 2:1 ratio to the web-based stress management intervention (n = 329) or the waitlist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 37 publications
4
69
0
1
Order By: Relevance
“…Participants in the present study also completed more than half (56%) of the available additional present perceived control exercises on average. These rates are comparable to or higher than completion rates for a similar intervention in college student samples 17 .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Participants in the present study also completed more than half (56%) of the available additional present perceived control exercises on average. These rates are comparable to or higher than completion rates for a similar intervention in college student samples 17 .…”
Section: Discussionmentioning
confidence: 61%
“…The average effect size across four outcomes was small to moderate. Additional clinical trials have further established the efficacy of the perceived control intervention for reducing stress-related symptoms [16][17][18][19] . Increases in perceived present control also appeared to be the mechanism of change in symptoms 15,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first RCTs tested the efficacy of our intervention in general samples of college students and found that it was effective in reducing symptoms of stress, anxiety, and depression and that increases in present control mediated decreases in symptoms (Frazier et al, 2015;Hintz, Frazier, & Meredith, 2015). In a subsequent study, we found that our intervention was more effective for students exposed to IPV, including sexual assault, than for those not exposed (Nguyen-Feng et al, 2015). Rather than offering a trauma-focused intervention specifically to students with an IPV history, we were able to reach those students by offering a general stress management intervention to a large group of students, 39% of whom had an IPV history.…”
Section: Interventions Addressing Meaning Makingmentioning
confidence: 83%
“…Apesar de ser mais recente que outros modelos e tipologias relacionadas a controle encontradas na literatura e amplamente citadas, tais como controle comportamental, controle cognitivo e controle de decisão (Averill, 1973), controle primário e controle secundário (Rothbaum, Weisz, & Snyder, 1982), lócus de controle interno e externo (Rotter, 1966), o modelo temporal apresentado por Frazier et al (2011Frazier et al ( , 2001) tem sido citado e utilizado em diversos estudos (p.ex., Frazier, 2003;Frazier et al, 2012;Hintz, Frazier, & Meredith, 2015;Misono, Meredith, Peterson, & Frazier, 2015;Nguyen-Feng et al, 2015;Sirois, Davis, & Morgan, 2006).…”
Section: Modelo Temporal De Controle Percebidounclassified